2008
DOI: 10.1086/590906
|View full text |Cite
|
Sign up to set email alerts
|

SWIFT J1753.5-0127: A Surprising Optical/X-Ray Cross-Correlation Function

Abstract: We have conducted simultaneous optical and X-ray observations of SWIFT J1753.5Ϫ0127 with RXTE and ULTRACAM, while the system persisted in its relatively bright low/hard state. In the cross-correlation function, we find that the optical emission, with a broad negative peak, leads the X-ray emission by a few seconds and has a smaller positive peak at positive lags. This is markedly different from what was seen for the similarly interesting system XTE J1118ϩ480, and it is the first time that such a correlation fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
77
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 14 publications
(21 reference statements)
13
77
1
Order By: Relevance
“…Extrapolating this power law to optical/NIR wavelengths shows that a spectral break is required at optical/UV frequencies. Analysis of optical data of Swift J1753.5−0127 in its current state by Hynes et al (2009) favors a case where any jet emission is insignificant at optical wavelengths consistent with our extrapolated power-law; this is in agreement with an independent observation/analysis by Durant et al (2008Durant et al ( , 2009). Gandhi (2009) has shown, based on analysis of optical data from XTE J1118+480, GX 339−4, and Swift J1753.5−0127 that the variability at optical wavelengths is inconsistent with being produced by reprocessing of X-rays in the accretion disk and instead favor a model where the emission in the LHS is dominated by the jet, e.g., Malzac et al (2004).…”
Section: Jet And/or Coronasupporting
confidence: 89%
“…Extrapolating this power law to optical/NIR wavelengths shows that a spectral break is required at optical/UV frequencies. Analysis of optical data of Swift J1753.5−0127 in its current state by Hynes et al (2009) favors a case where any jet emission is insignificant at optical wavelengths consistent with our extrapolated power-law; this is in agreement with an independent observation/analysis by Durant et al (2008Durant et al ( , 2009). Gandhi (2009) has shown, based on analysis of optical data from XTE J1118+480, GX 339−4, and Swift J1753.5−0127 that the variability at optical wavelengths is inconsistent with being produced by reprocessing of X-rays in the accretion disk and instead favor a model where the emission in the LHS is dominated by the jet, e.g., Malzac et al (2004).…”
Section: Jet And/or Coronasupporting
confidence: 89%
“…Hence, the spectral model also predicts the connection between the OIR and the X-ray aperiodic variability. However, simultaneous analysis of light curves in these wavelengths (Motch et al 1983;Kanbach et al 2001;Hynes et al 2003;Durant et al 2008;Gandhi et al 2010) has revealed a complicated connection between them, which can be understood if one considers several components contributing to the optical (Veledina et al 2011), namely the hot accretion flow and the reprocessed radiation. Additionally, the jet optically thin synchrotron emission can also be significant (e.g., Casella et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are three possible candidates that may account for this emission: the irradiated disc (Cunningham 1976;Gierliński et al 2009), hot accretion flow (Veledina et al 2013a) and the jet (Hynes et al 2002;Gallo et al 2007). Sometimes the OIR fluxes are higher than expected from any candidate alone (Chaty et al 2003;Gandhi et al 2010), and the complex optical/X-ray cross-correlation functions ⋆ E-mail: juri.poutanen@utu.fi (Kanbach et al 2001;Durant et al 2008) support this anticipation, suggesting contribution of two components simultaneously (Veledina, Poutanen, & Vurm 2011b). The source of OIR emission cannot be determined by only using photometric data and some additional information about the OIR-X-ray connection, short time-scale variability properties and the long-term spectral variations is required (see review in Poutanen & Veledina 2014).…”
Section: Introductionmentioning
confidence: 99%